Relationship between Serum IgE and Frequent Relapse Idiopathic Nephrotic Syndrome - Jahan, I; Hanif, M; Ali, MA; Waliullah, SM; Mia, AH (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):484-489 The abstract of this article is available on the PubMed website